Reporting Abuse: A Study of the Perceptions of People with Disabilities (PWD) Regarding Abuse Directed at PWD - West, Bernadette; Gandhi, Sampada (Disability Studies Quarterly, 2006)
Critical theory is useful in understanding the position of people with disabilities (PWD) in society. This theoretical framework suggests that there is an unequal distribution of resources and power in society, which produces both conflict between groups as a consequence of this inequality and marginalization of those without resources and power. Evidence of the marginalization of PWD can be found in research that suggests that PWD experience abuse at rates 4 to 10 times higher than the rate for people without disabilities. The rate of abuse directed at people with disabilities (PWD) is often hard to document for many reasons including the fact that historically data on disability status has not been collected in databases tracking crime and victimization. Furthermore, the media often fails to cover these situations, keeping the problem hidden from view. Another factor in the hidden nature of abuse is that research suggests PWD often cannot or chose not to report abuse and when they do report, their claims are often disregarded. The goal of our research was to develop a better understanding of abuse directed at PWD–from their perspective. In focus groups with PWD, we explored the question of whether PWD report abuse, and if so to whom do they report and what was the outcome. Then using content analysis and Atlas.ti software we coded transcripts of the focus groups for major themes. The comments of participants suggest that PWD do report abuse–primarily to family, police and agency staff. However, they also say these social support systems often do not believe them or discount their reports because of their disability status. When they chose not to report, it is because they feel they will not be believed, they are fearful of further reprisal or losing a needed caretaker, and consequently are willing to tolerate a certain level of abuse. While participants often described some kind of follow-up to their reports, few were certain what happened eventually to the abuser. The findings suggest the importance of including the perspective of affected populations in attempts to understand an issue such as abuse. They also suggest the need for training programs that teach PWD about their rights and strengthens their skills as self-advocates, as well as training efforts directed at caregivers and the police.